Materials advances through aberration-corrected electron microscopy - Pennycook, S; Varela, M; Hetherington, C; Kirkland, A (2006)
Over the last few years, the performance of electron microscopes has undergone a dramatic improvement, with achievable resolution having more than doubled. It is now possible to probe individual atomic sites in many materials and to determine atomic and electronic structure with single-atom sensitivity. This revolution has been enabled by the successful correction of the dominant aberrations present in electron lenses. In this review, the authors present a brief overview of these instrumental advances, emphasizing the new insights they provide to several areas of materials research.